2012
DOI: 10.1111/j.1756-185x.2012.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and its determinants in Malaysian women with rheumatoid arthritis

Abstract: We found in this study that the prevalence of FSD in rheumatoid arthritis in our centers was 29.4%. Age and family dynamics appear to be more important predictors compared to disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 23 publications
7
29
1
Order By: Relevance
“…The most affected dimensions of sexuality were: lower scores in the domains of desire, arousal, orgasm and satisfaction in women with RA than in controls. Our results are approximately similar to those found in the literature [1720]. The percentage of RA patients experiencing sexual problems ranged in previous studies from 29 to 76% [17, 18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The most affected dimensions of sexuality were: lower scores in the domains of desire, arousal, orgasm and satisfaction in women with RA than in controls. Our results are approximately similar to those found in the literature [1720]. The percentage of RA patients experiencing sexual problems ranged in previous studies from 29 to 76% [17, 18].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are approximately similar to those found in the literature [1720]. The percentage of RA patients experiencing sexual problems ranged in previous studies from 29 to 76% [17, 18]. To the best of our knowledge, there were few RA studies using FSFI as a measure of sexual dysfunction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Panush et al 39 demonstrated that in 85% of their patients, the increased disease activity with joint swelling was a major limiting factor for initiating sexual activity. Furthermore, Shahar et al 40 showed significant correlation between sexual function index score (assessed by Malay Version of FSFI) with erythrocyte sedimentation rate (r=-0.364, p=0.009) and disease activity score in 28 joints (r=-0.268, p=0.057), patient's age (r=0.520, p<0.001), duration of marriage (r=-0.355, p=0.001), husband's age (r=-0.460, p=0.001), age of oldest child (r=-0.449, p=0.001), and age of youngest child (r=-0.627, p<0.001). Yilmaz et al 41 reported a strong negative correlation between total female sexual function score with disease activity scores in 28 joints, a moderate negative correlation between total female sexual function score with HAQ, BDI, visual analog scale scores, age, and morning stiffness and weak negative correlation between total female sexual function score and body mass index in females with RA.…”
Section: Discussionmentioning
confidence: 99%
“…El Miedany et al [22] found that pain was the least contributing domain in patients with RA with SD (73%), whereas orgasmic disorder was the most prevalent (96.8%). Shahar et al [27] revealed that satisfaction domain was the most affected among patients with RA (49%), and orgasm was the least affected domain (7.8%). Besides, Lin et al [18] revealed highest standardized score (mean/total score '%') with satisfaction domain, whereas arousal showed the lowest standardized score.…”
Section: Discussionmentioning
confidence: 99%